Some considerations on the formal structure of freudian metapsychology - Baldini, Franco; Ceschi, Maria Vittoria; Meroni, Edoardo (Metapsychologica - rivista di psicanalisi freudiana, 2022)
We will present a few brief general considerations about metapsychology, with particular reference to the arguments put forward in Volker Hartmann Cardelle and Dietmar Dietrich's essay in this issue of the journal. In particular we demonstrate that, in opposition to the claims of many psychoanalysts and experts, the differences between the metapsychology model and the model of the Project are substantial. These depend on the radical change in Freud's approach to the problem of the mind. We show that a proper neurobiological reduction of metapsychology is impossible. We also show that any parallelism between computer science and metapsychology becomes inadmissible if we consider the mind only in terms of its relationship with an organic substrate. It will also be shown how, despite the fact that the link between physics and metapsychology is generally regarded as a mere analogy, the metapsychological model is actually a physical model. It is specifically physics and not for example computer science, which can provide an important aid to a better understanding and development of metapsychology. Finally, although any possible formalization of metapsychology is undoubtedly useful and desirable, we maintain that such formalism must again be translatable into natural language given that the unique character of psychology is that it contains both the instrument for and the object of investigation.